Skill Development in Rural Area- Challenges & Opportunities - Dr. Priyanka Gupta (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
India is the youngest nations in the world, with more than 54% of the total population below 25 years of age and over 62% of the population in the working age group (15-59 years). Good quality of demographic dividend is also available here for growth of country. In urban areas, more opportunities are available for skill development but in rural areas, no chance available for skill development with changing demands of time while India lives in its villages because nearly 70% population lives in rural area. Agriculture is a major source of earning for all families in rural area. In agriculture sector, Disguised Unemployment is a barrier for development of country. India is having more potential for standing in queue of developed country through better implementation of skill development programme if provide proper attention on especially rural areas because we can divert work force in service sector with help of skill development programme. Skill Development, Knowledge and Information & Communication Technology, these three are important conditions for bringing new changes in rural areas. In real word, at the time of making policies by government, rural areas consider as an engine of economy but unfortunately, India’s rural area is still fighting for own development. After changing of present scenario in rural areas than we can expect about to empower India. In rural areas, if one side more opportunities available as more work force, raw material, sufficient place, etc. and other side more challenges also available here as unemployment, lack of vocational education, lack of training programmes, lack of proper work conditions, etc. In this paper, opportunities & challenges are highlighted for the purpose of better implementation of skill development in rural areas. If skill development programme successfully implemented in rural areas, India will be powerful within short period. Keyword- Skill Development, Rural area, India, Economy.